HIMSS dictionary of health information and technology terms, acronyms and organizations. - Healthcare Information and Management Systems Society (New York : Routledge, 2024)
"This significantly expanded and newest edition of the bestselling HIMSS dictionary of health information technology terms, acronyms, and organizations has been developed and extensively reviewed by a robust team of industry experts. The fifth edition of this dictionary serves as a quick reference for students, health information and technology (IT) professionals and healthcare executives to better navigate the ever-growing health IT field."--Back cover.
"A Productivity Press book."
Keywords: Medical informatics -- Dictionaries; Medical informatics -- Terminology; Medical informatics; Medicine -- Data processing; BUSINESS & ECONOMICS / Quality Control; BUSINESS & ECONOMICS / Human Resources & Personnel Management